2019
DOI: 10.1186/s12544-019-0371-7
|View full text |Cite
|
Sign up to set email alerts
|

Truck-bicycle safety: an overview of methods of study, risk factors and research needs

Abstract: The growing numbers of cyclists either injured or killed in accidents caused by trucks have been generally regarded as a safety problem since the 1980s (McCarthy & Gilbert, Accident Analysis & Prevention 28:275-279, 1996). Indeed, in several countries, cyclists killed by a truck represent almost 30% of all cycling fatalities (Pokorny et al., Transportation Research Procedia, 25, 2017). Whilst increasing attention has been paid to this topic by road safety researchers, a scoping review of the current research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The popular research trend today involves exploring the safety of bicycle (and at the same time PMV) routes [43][44][45]. Many researchers have put efforts into establishing methods to explicitly address bicycle safety by reflecting urban conditions, and have found that many factors influence safety, including the traffic volume, lane width, population density, highway classification, presence of vertical grades, one-way streets, and truck routes [21].…”
Section: Pmvs and Road Safetymentioning
confidence: 99%
“…The popular research trend today involves exploring the safety of bicycle (and at the same time PMV) routes [43][44][45]. Many researchers have put efforts into establishing methods to explicitly address bicycle safety by reflecting urban conditions, and have found that many factors influence safety, including the traffic volume, lane width, population density, highway classification, presence of vertical grades, one-way streets, and truck routes [21].…”
Section: Pmvs and Road Safetymentioning
confidence: 99%
“…Popular research trend today is exploring the safety of bicycle (and at the same time PMV) routes (Boss et al, 2018;Prati et al, 2018;Pokorny & Pitera, 2019). Many researchers put efforts in establishing the methods to explicitly address bicycle safety by reflecting urban conditions, and have found that many factors influence the safety, starting from traffic volume, lane width, population density, highway classification, presence of vertical grades, one-way streets, and truck routes (Lawrence, 2016).…”
Section: Pmvs and Road Safetymentioning
confidence: 99%
“…Therefore, his study suggested the need for a new standard of window design and shape which defines what should be visible through direct vision from the vehicle. [8] mean while conduct a research on the lorry-bicycle safety. In their findings, they identified several risk factors that lead to accident between the lorry and bicycle.…”
Section: Literature Reviewmentioning
confidence: 99%